2014
DOI: 10.1002/oby.20732
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of spontaneous physical activity and sedentary behavior to prevent weight regain in older adults

Abstract: Objective This study determined whether adding a self-regulatory intervention (SRI) focused on self-monitoring of spontaneous physical activity and sedentary behavior to a standard weight loss intervention improved maintenance of lost weight. Design and Methods Older (65–79 yrs), obese (BMI=30–40 kg/m2) adults (n=48) were randomized to a five-month weight loss intervention involving a hypocaloric diet (DIET) and aerobic exercise (EX) with or without the SRI to promote spontaneous physical activity and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 36 publications
0
49
0
1
Order By: Relevance
“…Twelve studies reported on outcomes related to physical activity [2940] and 11 on outcomes related to weight [2729,3137,39]. Four trials were conducted with older adults; five with overweight, obese, or sedentary adults; three with participants with a chronic medical illness (e.g., chronic obstructive pulmonary disease, metabolic disease, diabetes); and two with healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies reported on outcomes related to physical activity [2940] and 11 on outcomes related to weight [2729,3137,39]. Four trials were conducted with older adults; five with overweight, obese, or sedentary adults; three with participants with a chronic medical illness (e.g., chronic obstructive pulmonary disease, metabolic disease, diabetes); and two with healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Two small trials judged to be at high risk of bias compared accelerometer interventions with active comparators [29,31]. While both trials demonstrated a positive trend of weight loss (MD −3.60 to −2.10), only one study [31] was statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Blood levels of the activity related neuropeptide orexin (discussed below) are higher among people with higher amounts of physical activity [23]. Few intervention studies have addressed the clinical significance of elevated SPA to human obesity or addressed whether an increase in SPA mitigates weight gain in the predicted manner by increasing total energy expenditure in adults [24, 25]. Despite the limitations that were acknowledged in those studies [24, 25], the difficulty of designing SPA interventions may be related to the inherent difficulty of intervening to increase SPA levels based on its operational definition as low intensity physical activity that distinguishes this “non-exercise physical activity” from formal exercise.…”
Section: Human Spa Studiesmentioning
confidence: 99%
“…Nicklas et al, (2014), determined whether adding a self-regulatory intervention focused on self-monitoring of spontaneous physical activity and sedentary behavior to a standard weight loss. To do this, the sample was divided into two groups, one that made diet plus aerobic exercise and the other that was dieting, aerobic exercise and was instructed to improve spontaneous physical activity and decrease sedentary behaviour.…”
Section: Discussionmentioning
confidence: 99%